Microangiopathy in inflammatory diseases: strategies in surgery of the lower extremity - Biehl, Christoph; Biehl, Lotta; Tarner, Ingo Helmut; Müller-Ladner, Ulf; Heiß, Christian; Heinrich, Martin (Life, 2022)
Background: Patients with an inflammatory disease frequently develop chronic angiopathy of the capillaries. Due to this pathology, there is an increased rate of complications in lower extremity surgical procedures. It is not uncommon for microangiopathic wound healing disorders to cause deep infections and fistulas, which lead to prolonged courses and hospitalizations. In addition, adhesions and ossifications of the contractile elements occur regularly. This sometimes results in serious limitations of the mobility of the patients. The study aims to present the results of a combination of vacuum and physical therapy. Patient and methods: A retrospective study of six patients with systemic sclerosis undergoing joint-related procedures of the lower extremity between 2015 and 2020 was performed. In addition to characterization of the patients and therapy, special attention was paid to cutaneous wound healing, affection of the fascia and displacement layers, and sclerosis of the muscle and tendon insertion. Results: The characterized structures (skin, tendon, fascia) show pathological changes at the microangiopathic level, which are associated with delayed healing and less physical capacity. Early suture removal regularly results in secondary scar dehiscence. With a stage-adapted vacuum therapy with sanitation of the deep structures and later on a dermal vacuum system, healing with simultaneous mobilization of the patients could be achieved in our patient cohort. Conclusion: In the case of necessary interventions on the lower extremity, such as trauma surgery, additional decongestive measures in the sense of regular and sustained lymphatic therapy and adapted physiotherapy are indispensable.